Bi25feo40 polycrystalline ceramic as highly efficient photocatalyst synthesised via economical chemical route - Verma M.K.; Kumar A.; Singh L.; Sonwani R.K.; Das T.; Singh S.; Kumar V.; Singh N.B.; Mandal K. (My University, 2025)
Bi25FeO40 (BFO) polycrystalline ceramic was synthesised by soft chemical route at lower sintering temperature for investigation of photocatalytic activity with respect to adsorption of methylene blue in the presence of UV-VIS irradiation. The single phase formation of BFO ceramic was confirmed by powder X-ray diffraction studies and particle size observed by TEM measurement was found to be 25 ± 5 nm which reveals the nanocrystalline nature of the materials. Additionally, photocatalytic activity of Bi25FeO40 was evaluated by the degradation of Methylene blue (MB) under visible light. It displayed higher photocatalytic activity than other synthesised materials like as BiFeO3 as well as TiO2 due to smaller band gap (1.8 eV). Furthermore, process variables such as pH, process time, and Bi25FeO40 dose were optimised and found to be 10, 30 min, and 0.8 mg/L, respectively. Kinetic study reveals that the adsorption process of BFO ceramic obeys pseudo-second-order kinetics. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.